Effectiveness and safety of aerobic exercise for rheumatoid arthritis: a systematic review and meta-analysis of randomized controlled trials - Hui Ye; Heng Weng; Yue Xu; Lulu Wang; Qing Wang; Guihua Xu (BMC, 2022)
Abstract Background Rheumatoid arthritis (RA) can cause severe physical impairment and a reduced quality of life, and there is limited evidence for any effective intervention. Aerobic exercise may be beneficial for improving symptoms. Therefore, the purpose of this meta-analysis was to evaluate the effectiveness and safety of aerobic exercise for rheumatoid arthritis patients. Methods PubMed, The Cochrane Library, Web of Science, EMBASE, CNKI, WanFang Data and VIP databases were searched. Randomized controlled trials of the effectiveness and safety of aerobic exercise for rheumatoid arthritis were included. Risks of bias were assessed by two independent reviewers using the methods described in the RevMan 5.3, GRADEpro and the Cochrane Handbook. Meta-analyses were performed to investigate the effects of aerobic exercise on rheumatoid arthritis. Results A total of 13 RCTs were included, including 967 rheumatoid arthritis patients. The Meta-analysis results showed that aerobic exercise can improve functional ability [MD = − 0.25, 95% CI (− 0.38, − 0.11), P = 0.0002], relieve pain [SMD = − 0.46, 95% CI (− 0.90, − 0.01), P = 0.04], increase aerobic capacity [MD = 2.41, 95% CI (1.36, 3.45), P < 0.00001] and improve the Sit to Stand test score[MD = 1.60, 95% CI (0.07, 3.13), P = 0.04] with statistically significant differences. Conclusion Generally, aerobic exercise is beneficial and safe for RA patients and has a certain alleviating effect on the disease, such as functional ability improvement, pain relief and aerobic capacity increase. Limited by the quantity and quality of the included studies, future research with higher-quality studies needs to be conducted to verify the above conclusions. Trial registration: PROPERO registration number: CRD42021242953.